2014
DOI: 10.3389/fpls.2014.00569
|View full text |Cite
|
Sign up to set email alerts
|

The Malus domestica sugar transporter gene family: identifications based on genome and expression profiling related to the accumulation of fruit sugars

Abstract: In plants, sugar transporters are involved not only in long-distance transport, but also in sugar accumulations in sink cells. To identify members of sugar transporter gene families and to analyze their function in fruit sugar accumulation, we conducted a phylogenetic analysis of the Malus domestica genome. Expression profiling was performed with shoot tips, mature leaves, and developed fruit of “Gala” apple. Genes for sugar alcohol [including 17 sorbitol transporters (SOTs)], sucrose, and monosaccharide trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
102
2
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(119 citation statements)
references
References 51 publications
(136 reference statements)
7
102
2
8
Order By: Relevance
“…Similarly, Wei et al . () found that the expression of the MdSWEET4.1 transporter (phylogenetically similar to AtSWEET17) was higher in the leaves than in the fruit of apple trees, and that the fructose concentration was lower in the leaves. The AtSWEET17 transporter is a bidirectional passive transporter (Guo et al ., ), and its activity corresponds with the TpassifFru parameter of the model.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Wei et al . () found that the expression of the MdSWEET4.1 transporter (phylogenetically similar to AtSWEET17) was higher in the leaves than in the fruit of apple trees, and that the fructose concentration was lower in the leaves. The AtSWEET17 transporter is a bidirectional passive transporter (Guo et al ., ), and its activity corresponds with the TpassifFru parameter of the model.…”
Section: Discussionmentioning
confidence: 99%
“…Sixty to eighty percent of Sor is produced in apple leaves and almost all Sor and half of Suc are converted to Fru, estimating that 80% of total carbon flux is due to Fru production in fruit . Many MS identifications (listed in Supporting Information Table 1 using Uniprot_ Malus database) are proteins involved in sugar cycle and transport: Sorbitol‐6‐phosphate dehydrogenase (A0A0S1TQH9_MALDO) converts Sor after being taken up into the cytosol of parenchyma cells, into Fru imported in vacuole for accumulation . The balance between sugar and organic acids, due to both glycolysis and TCA cycle, is largely responsible for apple flavor: the most predominant organic acids are malic acid and citric acid, which decrease their abundance during maturation process .…”
Section: Discussionmentioning
confidence: 99%
“…During papaya fruit development, this organ represents a strong sink of the sugars and water, which allows the fruit to grow. The fruit receive the main sugars by long-distance transport by phloem and sugar accumulations requiring the operation of transporters due to their size and polarity (Wei et al, 2012). The accumulation of sugars in the fruit is directly related to the active transport of hexoses and the synthesis and metabolism of sugars (Zhou and Paull, 2001;Paull et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The transport of sugar and other solutes into the cell may occur by plasmodesmatas or sugar transporters by the H + /sugar symporter or antiporter, respectively, in the plasma membrane and tonoplast (Lalonde et al, 1999;Ruan, 2014). According to Wei et al (2012), three families of transporters-SUTs, MSTs (or HT), and SWEETs-are mainly implicated in the distribution of sugars within most plant cells. The plant sugar transporters are proton coupled energy-dependent, with stoichiometry of H + /sucrose cotransport determined as 1:1 (Lalonde et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation